Torsion of a herniated ovary in an infant: a case report - Ismail Benomar; Hidaya Zitan; Loubna Aqqaoui; Ali Lahrech; Houda Oubejja; Fouad Ettayebi (Journal of Pediatric Surgery Case Reports)
Introduction: Inguinal hernias are relatively common in newborns; however, herniation of the ovary through the canal of Nuck is a rare condition that can lead to ovarian torsion and infarction if not promptly managed. Case presentation: We report the case of a 3-month-old female infant, born at term following an uneventful pregnancy and neonatal period, with normal growth parameters and psychomotor development. She presented with a non-reducible, tender right inguinal mass associated with local signs of inflammation. Symptoms had been evolving over five days. Doppler ultrasonography revealed an enlarged, heterogeneous ovarian structure with absent vascular flow, indicative of adnexal torsion. Surgical exploration confirmed torsion of the right fallopian tube and a necrotic ovary within an inflamed hernia sac. A right salpingo-oophorectomy was performed. The patient was discharged 24 hours postoperatively. Histopathological examination revealed ovarian gangrene without evidence of neoplastic or dysplastic changes. Postoperative recovery was uneventful, and no complications were observed at the 3-month follow-up. Conclusion: Ovaries herniated into the inguinal canal require prompt reduction and hernia repair to avoid potential complications such as torsion and infarction, as observed in our patient.